Discrete element modelling of flexible fibre packing - Langston, Paul; Kennedy, Andrew R.; Constantin, Hannah (Elsevier, 2015)
This paper presents Discrete Element Model simulations of packing of non-cohesive flexible fibres in a cylindrical vessel. No interstitial fluid effects are modelled. Each fibre-particle is modelled as a series of connected sphero-cylinders. In an initial study each particle is modelled a single rigid sphero-cylinder; the method has been used before but this study considers higher aspect ratios up to 30. This posed some modelling challenges in terms of stability which were overcome by imposing limits on the particle angular velocity. The results show very good agreement with experimental data in the literature and more detailed in-house experiments for packing volume fraction. Model results on particle orientation are also shown. The model is developed to include flexibility by connecting sphero-cylinders as sub-elements to describe a particle. Some basic tests are shown for the joint model that connects the sub-elements. The simulation results show similar trends to the rigid particle results with increased packing fraction. The effects of number of sub-elements, joint properties and contact friction are examined. The model has the potential for predicting packing of fibrous particles and fibre bundles relevant to the preparation of preforms for the production of discontinuously-reinforced polymer, ceramic and metallic matrix composites.